Structuring of Goals and Plans for Personalized Planning and Integrated Testing of Plans - Sedrak H. Grigoryan (Изд-во НАН РА)
We study competition problems defined in the class where Space of Solutions is a Reproducible Game Tree (RGT). Personalized Planning and Integrated Testing algorithms were developed for searching optimal strategies in RGT problems.
Keywords: Mathematics; Science; Algorithm